The Clint Eastwood westerns - Neibaur, James L., 1958- (Rowman and Littlefield, 2015)
This book looks at the film and television genre that made Clint Eastwood a star: westerns. The author discusses in detail the production, impact, influences, and successes (both critical and commercial) of each of Eastwood's films. Neibaur also examines the continued success and influence of his films on the western film genre.